Probability distributions of arsenic in soil from brownfield sites in Beijing （China）： statistical characterization of the background populations and implications for site assessment studies - Marina ACCORNERO Lin JIANG Eugenio NAPOLI Marco CREMONINI Giovanni FERRO Federica BELLORO Maosheng ZHONG (中国环境科学与工程前沿：英文版, 2015)
A probabilistic analysis was performed on soil arsenic concentration data from 4 brownfield sites at Beijing （Chaoyang and Haidian Districts）, involved in environmental assessment studies. The available data sets were processed to provide a statistical characterization of the background populations and differentiate ＂anomalous data＂ from the natural range of variation of arsenic concentrations in soil. The site-specific background distributions and the existing wide-scale background values defined for the Beijing area were compared, discussing related implications for the definition of metal contamination soil screening levels （SSLs） in site assess- ment studies. The statistical analysis of As data sets discriminated site-specific background populations, encompassing 88% to 94% of the sample data, from oufliers values, associated with either subsoil natural enrichments or possible anthropogenic releases. Upper Baseline Concentration （UBC） limits （＋ 2σ level）, including most of the site-specific metal background variability, were derived based on the statistical characterization of the background populations. Sites in the Chaoyang South District area had UBC values in the range 10.4-12.6mg·kg^-1. These ranges provide meaningful SSL values to be adopted for As in local site assessment studies. Using the wide-scale background value for the Beijing area would have erroneously classified most of the areas in the subject sites as potentially contaminated.